PREPARATION FOR THE MENARCHE PERIOD FOR ADOLESCENT - Agus Sulistyowati, S.Kep., M.Kes; Sri Wiji Lestari (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Menarche is the first menstruation that usually occurs in the age range of 10-16 years or in early adolescence in the middle of puberty before entering the reproductive period. So far, some people feel taboo to talk about menstrual problems in the family, so that early adolescents do not have sufficient knowledge and attitudes about the physical and psychological changes of menarche (Proferawati, 2009). Implementation of counseling activities on January 31, 2023 at Pucang 4 Sidoarjo Elementary School. Target of this counseling activity is students of class 5 and 6 at Pucang 4 Sidoarjo Elementary School. Prior to carrying out extension activities, there is a process of preparing activities for approximately three weeks prior to implementation activities, starting from determining the type of extension to applying for permits to related parties. As a form of evaluation, the activity was attended by 60 grade five and six students, the participants took part in the activity with very enthusiasm, and the counseling activities ran smoothly. Keywords: Menarche Periode, Education, Counseling, Elementary School Students.